1997
DOI: 10.1103/physrevlett.79.2053
|View full text |Cite
|
Sign up to set email alerts
|

Suprathermal Electron Generation and Channel Formation by an Ultrarelativistic Laser Pulse in an Underdense Preformed Plasma

Abstract: Relativistic electrons are produced, with energies up to 20 MeV, by the interaction of a high-intensity subpicosecond laser pulse (1 mm, 300 fs, 10 19 W͞cm 2 ) with an underdense plasma. Two suprathermal electron populations appear with temperatures of 1 and 3 MeV. In the same conditions, the laser beam transmission is increased up to 20%-30%. We observe both features along with the evidence of laser pulse channeling. A fluid model predicts a strong self-focusing of the pulse. Acceleration in the enhanced lase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(45 citation statements)
references
References 25 publications
2
42
1
Order By: Relevance
“…Initial experimental studies (2)(3)(4)(5), conducted close to the threshold condition of the channeling phenomenon (6)(7)(8)(9)(10)(11)(12)(13)(14)(15), have furnished evidence supporting this conclusion. Measurements of the spatial properties of the propagation, using both x-ray (4) and Thomson (16,17) images, have clearly established the formation of long channels of the form shown in Fig.…”
mentioning
confidence: 87%
“…Initial experimental studies (2)(3)(4)(5), conducted close to the threshold condition of the channeling phenomenon (6)(7)(8)(9)(10)(11)(12)(13)(14)(15), have furnished evidence supporting this conclusion. Measurements of the spatial properties of the propagation, using both x-ray (4) and Thomson (16,17) images, have clearly established the formation of long channels of the form shown in Fig.…”
mentioning
confidence: 87%
“…8,9,[13][14][15] A two-temperature distribution in the electron energy spectrum was reported by Malka et al 15 They attributed such a distribution to be a result of the combination of two different acceleration mechanisms, i.e., acceleration by a laser field and by a plasma wave. Gordon et al 16 have observed the acceleration of electrons beyond the linear dephasing limit, and explained it, using Particle-In-Cell ͑PIC͒ simulations, as a result of acceleration in wakefields driven by accelerated electrons.…”
Section: Introductionmentioning
confidence: 94%
“…Several groups [13,14] have claimed to observe plasma-density-depression channels produced in this way. However, these experiments did not present quantitative measurement of the evolution of a plasma waveguide and so other underlying mechanisms, such as thermal shock blowout after anomalously strong laser heating, were not experimentally ruled out.…”
Section: Evolution Of a Plasma Waveguide Created During Relativistic-mentioning
confidence: 99%
“…However, this driving force, =͑kT e ͒, is negligible compared to the ponderomotive driving force, =͑F p ͒, because the electron temperature kT e (Ӎm e y 2 p Ӎ 10 keV, where y p is the phase velocity of the plasma wave) is much smaller than the ponderomotive potential F p (Ӎ300 keV), and the diameter of plasma wave and the laser focus are roughly the same. It is therefore believed that the mechanism of ponderomotive selfchanneling is dominant for this work and probably for that of [13][14][15] …”
Section: Evolution Of a Plasma Waveguide Created During Relativistic-mentioning
confidence: 99%